Phubbing as a Social Norm: Effects on Fear of Missing Out (FoMO) and Perceived Exclusion - Miguel Ángel Albalá-Genol; Edgardo Etchezahar; Talía Gómez-Yepes; Joaquin Ungaretti (Revista Latinoamericana de Tecnología Educativa)
Technology and social media have transformed the way we communicate, interact, and stay informed. Phubbing is a term that comes from two words «phone» and «snubbing» and represents the act of ignoring a person in a real life setting by paying attention to their cell phone. This behavior may be normalized or cause social difficulties in certain situations. The aim of this study was to analyze the levels of normative behavior and their relations with FoMO, feelings of social exclusion and the phubbing perceived scale. A cross-sectional study was conducted, and the participants were 1506 people in Argentina (50.79% identified as women and 49.21% as men), with an age range between 18 and 65 years old who completed an online survey. The results confirmed that phubbing is perceived as normative behavior in most of the participants, representing a predictor of phubbing in their social interactions. Relations were also found between the perceived normative phubbing and levels of Fear of Missing Out (FoMO) and feelings of social exclusion. Implications of the variables studied are discussed as possible predictors of phubbing and are to be considered in its approach. The study examines phubbing as a normative behavior in Argentina. No previous studies have been carried out in our country that consider Fear of Missing Out (FoMO), Feelings of Social Exclusion and Perceived Phubbing as predictor variables.